Estudo da influência do biodiesel de mamona como aditivo antioxidante para o biodiesel de girassol e soja - Silva, Hellyda Katharine Tomaz de Andrade (2011)
Biodiesel is a fuel made up by mono-alkyl-esters of long chain fatty acids, derived from vegetable oils or animal fat. This fuel can be used in compression ignition engines for automotive propulsion or energy generation, as a partial or total substitute of fossil diesel fuel. Biodiesel can be processed from different mechanisms. Transesterification is the most common process for obtaining biodiesel, in which an ester compound reacts with an alcohol to form a new ester and a new alcohol. These reactions are normally catalyzed by the addition of an acid or a base. Initially sunflower, castor and soybean oil physicochemical properties are determined according to standard test methods, to evaluate if they had favorable conditions for use as raw material in the transesterification reaction. Sunflower, castor and soybean biodiesel were obtained by the methylic transesterification route in the presence of KOH and presented a yield above 93% m/m. The sunflower/castor and soybean/castor blends were studied with the aim of evaluating the thermal and oxidative stability of the biofuels. The biodiesel and blends were characterized by acid value, iodine value, density, flash point, sulfur content, and content of methanol and esters by gas chromatography (GC). Also studies of thermal and oxidative stability by Thermogravimetry (TG), Differential Scanning Calorimetry High Pressure (P-DSC) and dynamic method exothermic and Rancimat were carried out. Biodiesel sunflower and soybean are presented according to the specifications established by the Resolution ANP no 7/2008. Biodiesel from castor oil, as expected, showed a high density and kinematic viscosity. For the blends studied, the concentration of castor biodiesel to increased the density, kinematic viscosity and flash point. The addition of castor biodiesel as antioxidant in sunflower and soybean biodiesels is promising, for a significant improvement in resistance to autoxidation and therefore on its oxidative stability. The blends showed that compliance with the requirements of the ANP have been included in the range of 20-40%. This form may be used as a partial substitute of fossil diesel